The Impact of Tower Base Transceiver Station (BTS) Infrastructure Development on the Resident Environment - Illahi Dinati, Fitria Nur; Edy Santosa, F Rooslan; Durrotun Nasihien, Ronny (International Journal of Engineering, Science and Information Technology, 2021)
The development of the telecommunications industry in Indonesia is extremely rapid. It can be seen from the telecommunications operator vendors who served as telecommunications specialist co-ops rivaling each other in giving the best service to seize the attention of the Indonesian citizen, which requires telecommunications needs. Numerous realities have developed in various regions stating that the existence of Base Tower Transceiver Station (BTS) has resistance from the residents, which are caused by health issues (radiation), safety issues, to the problem of social value. Moreover, some people from residents supported the construction of Base Tower Transceiver (BTS) since the rental price of land for the tower construction is quite high. This study uses primary data from 100 respondents. The analysis technique uses multiple linear regression analysis, which is processed using SPSS (Statistical Product and Service Solution). The next step is to test the validity, reliability, and examine the classical assumptions (including normality test, autocorrelation test, and heteroscedasticity test). In the end, it can be concluded that the people of Rungkut sub-district in Surabaya, mostly enjoyed the benefits of the construction of the existence of the Telecommunications Tower Infrastructure around them.